Increasing Employee Complaint Data Collection With The Ticketing System Helpdesk Application And Ticket Progress Monitoring - Viarsyah, Muhammad Iqbal; Meiriska, Ienda; Siregar, Dewi Immawati; Sartika, Devi (Journal of Research in Social Science and Humanities, 2023)
The purpose of writing this Final Report is to create a Web-Based Helpdesk Application with a Ticketing System and Integration of Progress Monitoring Features to Improve Action Data Collection on Employee Complaints for the Population Control and Family Planning Office of Muara Enim Regency which includes ticket data input, edit and delete ticket data, manage news and users, as well as viewing user logs data by Admin. While Users (Customers / Employees) can make tickets, view news and can see the status of ticket work. The method used for preparing this report is the SDLC Waterfall system development method. The process used to design this system is the Unified Modeling Language (UML) and uses the PHP framework programming language, namely Laravel and the MySQL database. This system is divided into 3 parts, namely Admin, technicians and Users (Customers / Employees). By making this application, it is hoped that it will be able to improve data collection on actions against employee complaints for the Population Control and Family Planning Office of Muara Enim Regency.Â Abstrak:Â Tujuan Penulisan Laporan Akhir ini adalah untuk membuat Aplikasi Helpdesk Berbasis Web Dengan Sistem Ticketing Dan Integrasi Fitur Pemantauan Progress Untuk Meningkatkan Pendataan Tindakan Terhadap Keluhan Karyawan Untuk Dinas Pengendalian Penduduk Dan Keluarga Berencana Kabupaten Muara Enim yang meliputi input data ticket, edit dan hapus data ticket, mengelola berita dan user, serta meliihat data user logs oleh Admin. Sedangkan User(Customer/Pegawai) dapat membuat tiket, melihat berita serta dapat melihat status pengerjaan ticket. Metode yang digunakan untuk pembuatan laporan ini adalah menggunakan metode pengembangan sistem SDLC Waterfall. Proses yang digunakan untuk mendesain sistem ini adalah Unified Modeling Language (UML) dan menggunakan Bahasa pemrograman framework PHP yaitu Laravel serta database MySQL. Sistem ini terbagi menjadi 3 bagian yaitu Admin, teknisi dan User (Customer/Pegawai). Dengan dibuatnya aplikasi ini diharapkan dapat Meningkatkan Pendataan Tindakan Terhadap Keluhan Karyawan Untuk Dinas Pengendalian Penduduk Dan Keluarga Berencana Kabupaten Muara enim.